Kompilasi kajian kes konservasi artifak - Zamrul Amri Zakaria; Malaysia. Jabatan Muzium (Kuala Lumpur : Jabatan Muzium Malaysia, 2011)
Methods of conserving artifacts and museum objects in Malaysia.
In Malay.
Keywords: Museum conservation methods -- Malaysia; Ordnance -- Conservation and restoration; Ordnance; Malaysia -- Antiquities -- Collection and preservation